A comparative study and mother brand influence on determining the consumer perception of diet coke and diet pepsi: a UK market perspective - Islam, Md. Tamzidul (© 2013 International Journals of Marketing and Technology (IJMT), 2016)
This article was published in the International Journals of Marketing and Technology (IJMT) [© 2013 International Journal of Marketing and Technology] and the definite version is available at : http://www.ijmra.us/project%20doc/IJMT_SEPTEMBER2013/IJMRA-3810.pdf The article website is at: http://www.ijmra.us/2013ijmt_september.php